Phlebotomines (Diptera, Psychodidae) in the Ribeira Valley Speleological Province - 1. Parque Estadual Intervales, state of São Paulo, Brazil - Galati,Eunice Aparecida Bianchi (2010)
The identification of the sandfly fauna and investigation of some ecological aspects of its populations in areas frequented by tourists of the PEI, an Atlantic forest reserve with many caves, were the objective of this study. Captures were undertaken monthly from January 2001 to December 2002, with automatic light traps installed in 13 ecotopes, including caves, forests, domiciliary and peridomiciliary environments, and by aspiration in armadillo burrows. Additionally, although not at regular intervals, Shannon traps were installed in forests and anthropic environments, aspirations were made on cave walls, among roots and fallen leaves, and some insects were captured while biting researchers. A total of 891 sandflies belonging to 21 species were captured. Six hundred specimens representing 19 species were captured with light traps, 215 in anthropic (2.24 insects/trap) and 385 in extra-domiciliary (1.46 insects/trap) environments. Brumptomyia troglodytes was the most abundant species (the Standardised Index of Species Abundance = 0.705). Pintomyia monticola predominated in the Shannon traps and showed anthropophilic and diurnal activity. Psathyromyia pascalei predominated in the aspirations; the largest number being in armadillo burrows. Eleven species were captured in caves; although some might be troglophiles, the majority used these ecotopes as resting places. Nyssomyia intermedia, Nyssomyia neivai and Migonemyia migonei, implicated in the transmission of cutaneous leishmaniasis in the Southeastern Brazilian region, were all found, though in such low densities as to suggest minimal risk of the disease in the PEI.